The onset and progression of alcohol use disorders: A qualitative study from Goa, India. Issue 1 (2nd January 2019) - Mackinnon, Nathalie; Bhatia, Urvita; Nadkarni, Abhijit
ABSTRACT: Quantitative evidence about the burden of alcohol use disorders (AUDs) needs to be complemented with a nuanced qualitative understanding of explanatory models to help supplement public health strategies that are too often steeped uncritically in biomedical models. The aim of this study was to identify the role of various factors in the onset and persistence of AUD and recovery from AUD. This was a qualitative study nested in a population cohort from Goa, India. In-depth interviews of men with incident, recovered, and persistent AUD covered topics such as changes in drinking habits over time, perceptions and experiences about starting/stopping drinking, and so on. Data were analyzed using thematic analysis. Reasons to begin drinking included social drinking, functional use of alcohol, stress, and boredom. Progression to problematic drinking patterns was characterized by drinking alone, alternating between abstinent and heavy drinking periods, and drinking based on the availability of finances. Some enablers to reduce/stop drinking included consequences of drinking lifestyle and personal resolve; some barriers included availability of alcohol at social events and stress. Some reasons for persisting heavy use of alcohol included lack of family support, physical withdrawal symptoms, peer pressure, stress, and easy availability. This article offers a strong conceptualization and nuanced understanding of AUD across a spectrum of developmental courses. This adds to the limited literature on explanatory models of AUD in India and identifies potential targets for prevention and treatment strategies for AUD in low- and middle-income country settings.